2006
DOI: 10.1002/ejlt.200500282
|View full text |Cite
|
Sign up to set email alerts
|

Composition and oxidative stability of soybean oil in mixtures with jojoba oil

Abstract: Improvement of the oxidative stability of soybean oil (SBO) by blending with jojoba oil (JO) was investigated. SBO in the presence of 5, 10, 15 and 20 wt-% of JO was subjected to accelerated storage at 60 7C. Peroxide values (PV), anisidine values (AV), UV absorption characteristics (K 232 and K 270 values), and headspace volatiles were determined to monitor the oxidative stability of oil samples. JO was effective in reducing the formation of hydroperoxides and volatile compounds in SBO. The effect was remarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…1, R = CH 3 ) and of soybean oil (Eq. 1, R = C 16 and C 18 hydrocarbon chains [5] [6,7]. In this context, the present study was initiated with the premise that doping with other trivalent cations, such as those of the transition metals, would lead to PMO catalysts with tunable basicities and higher catalytic activities for triglyceride transesterification.…”
Section: Introductionmentioning
confidence: 99%
“…1, R = CH 3 ) and of soybean oil (Eq. 1, R = C 16 and C 18 hydrocarbon chains [5] [6,7]. In this context, the present study was initiated with the premise that doping with other trivalent cations, such as those of the transition metals, would lead to PMO catalysts with tunable basicities and higher catalytic activities for triglyceride transesterification.…”
Section: Introductionmentioning
confidence: 99%
“…Although refi ned soybean oil is a good lubricant, it oxidises too readily for use in many applications. The problem of low resistance to oxidation and limited shelf-life can be overcome in many ways, such as chemical modifi cation (notably partial hydrogenation and epoxidation) [32][33][34][35], © Woodhead Publishing Limited, 2013 use of additives [36], interesterifi cation with palm oil, genetic modifi cation with C18:3 reduction [37][38][39] (see Section 5.3.1), or blending with jojoba oil (JO) [40]. The use of the epoxidation route is particularly interesting since it yields a material suitable for other use that can be further modifi ed by a ring opening reaction [41].…”
Section: Edible Vegetable Oil Sourcesmentioning
confidence: 99%
“…Soybean breeding lines with low linolenic acid content have yet to be commercialised (see Table 5.20); interesterifi cation greatly increases processing costs. Therefore, it is of interest to consider non-conventional natural lipid sources [42], as well as simple processes such as mixing [40,43,44]. The SBO pour point (PP) problem can be solved by blending with other fl uids such as synthetic oils with lower PP (compromising the biodegradability) or by means of chemical addition.…”
Section: Edible Vegetable Oil Sourcesmentioning
confidence: 99%
“…Torres et al 30 reported that major volatile compounds were hexanal, 2-heptenal, 2,4-decadienal, nonanal and 2,4-heptadienal in soybean oil after 10 days storage at 60 . Beltrán et al 31 reported that hexanal, E -2-heptenal, E -2-octenal, nonanal, E -2-nonenal, E,E -2,4-nonadienal and E,E -2,4-decadienal were the major aldehydes in almond oils during thermal oxidation at 100 .…”
Section: Thermal Treatment Oven Testmentioning
confidence: 99%
“…This observation was monitored in the cold-pressed oil oxidation at 60 29 wherein 2,4-hexadienal isomers took place an important part of the volatile oxidation compounds during oxidation of canola oil. These compounds were identified and their content were richer among the volatile oxidation products during thermal oxidation of soybean oil 30 and almond oil 31 .…”
Section: Thermal Treatment Oven Testmentioning
confidence: 99%